Maxent modeling for predicting the spatial distribution of three raptors in the Sanjiangyuan National Park, China. Issue 11 (20th May 2019) - Zhang, Jingjie; Jiang, Feng; Li, Guangying; Qin, Wen; Li, Shengqing; Gao, Hongmei; Cai, Zhenyuan; Lin, Gonghua; Zhang, Tongzuo
Abstract: Upland buzzard ( Buteo hemilasius ), Saker falcon ( Falco cherrug ), and Himalayan vulture ( Gyps himalayensis ) are three common large raptors in the Sanjiangyuan National Park (SNP), China's first national park. Among them, Upland buzzard and Saker falcon play a significant role in controlling plateau rodent populations and reducing the transmission of pathogens carried by rodents. The Himalayan vulture can provide services for the redistribution and recycling of nutrients in the ecosystem, and play an irreplaceable role in the celestial burial culture of Tibetans in China. Exploring their habitat suitability is important for the protection of the three raptors. Our research was based on the current distribution of Upland buzzard, Saker falcon, and Himalayan vulture that we had extensively surveyed in the Sanjiangyuan National Park from 2016 to 2017. Combined with the correlation analysis of environmental variables, we utilized maximum entropy model (MaxEnt) to evaluate and compare the habitat suitability of the three species in the Sanjiangyuan National Park. Elevation, climate, and human disturbance factors, which had direct or indirect effects on species survival and reproduction, were all included in the model. Among them, elevation was the most important environmental variables affecting the suitability of habitats of three species. Temperature‐related factor was another important predictor. The high (>60%) suitable habitat areas for Upland buzzard, Saker falcon, and Himalayan vulture were 73, 017.63, 40, 732.78, and 61, 654.33 km 2, respectively, accounted for 59.32%, 33.09%, and 50.08% of the Sanjiangyuan National Park and their total suitable area (i.e., the sum area of high and moderate habitats) reached 96.07%, 60.59%, and 93.70%, respectively. Besides, the three species have overlapping areas for the suitable habitats, which means that overlapping areas should be highly valued and protected. Therefore, understanding the distribution of suitable habitats of the three raptors can provide useful information and reasonable reference for us to put forward suggestions for their protection and regional management. Abstract : This study used the maxent model to assess the habitat suitability of Upland buzzard, Saker falcon, and Himalayan vulture in Sanjiangyuan National Park, China (China's first national park). This research might provide a scientific basis for the conservation and management of species in Sanjiangyuan National Park, while raptors as umbrella species can benefit other species when they are protected and concerned.